INVESTIGATION OF STABLE ISOTOPE OF 18O AND 2H IN SHALLOW GROUNDWATER FROM KARAWANG AREA - E. Ristin Pujiindiyati (Indonesian Journal of Chemistry, 2008)
Karawang area is well known as an agriculture area and 2% area is utilized for industries. Clean water demands increase due to developing industry development and population increasement. The origin of groundwater is necessary to keep the sustainability of water resources in this area. Stable isotopes such as 18O and 2H can be used as a parameter to trace the ground water origin. The methods used were Epstein-Mayeda and Zinc reduction for analysis 18O and 2H, respectively. Sampling period was conducted in major dry season in year 2002. The result showed that evaporation effect had influenced to the content of both isotopes in its shallow groundwater that caused a slope shift from its local meteoric line. The origin of its shallow groundwater was from rainwater infiltrating directly in less than 10 m altitude. Citarum River showed more depleted values in both isotopes compared to shallow groundwater and it indicated that its water might originate from spring at the altitude of 600 m.